2001
DOI: 10.1108/09513570110399890
|View full text |Cite
|
Sign up to set email alerts
|

The effect of thematic structure on the variability of annual report readability

Abstract: The readability of annual reports has been the focus of extensive prior research. However, the extent of readability variability has only recently received specific attention. In response to a perceived need for further research into this area, an analysis of 60 UK chairman's statements was conducted in order to test for possible determinants of readability variability. Results show the introduction to the chairman's statement is systematically easier to read than other parts of the chairman's statement. No ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
266
2
10

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(282 citation statements)
references
References 20 publications
4
266
2
10
Order By: Relevance
“…As shown in (Adelberg, 1979;Courtis, 1986;Jones, 1988;Baker and Kare, 1992;Kohut and Segars, 1992;Smith and Taffler, 1992a;Subramanian et al, 1993;Courtis, 1995Courtis, , 1998Clatworthy and Jones, 2001). …”
Section: Methods Of Content Analysis In Prior Impression Management Rmentioning
confidence: 99%
“…As shown in (Adelberg, 1979;Courtis, 1986;Jones, 1988;Baker and Kare, 1992;Kohut and Segars, 1992;Smith and Taffler, 1992a;Subramanian et al, 1993;Courtis, 1995Courtis, , 1998Clatworthy and Jones, 2001). …”
Section: Methods Of Content Analysis In Prior Impression Management Rmentioning
confidence: 99%
“…Clatworthy and Jones (2006) argued that extreme changes in FP can affect the thematic content of the narrative disclosure, such as the chairman's statement. Clatworthy and Jones (2001) found that profitable firms are more inclined to discuss their results and acquisitions and disposals, while unprofitable firms include more discussion of board changes. Clarke (1997: p. 36) found that "firms with negative results do divert attention away from themselves by referring to the environment, target markets and emotive words rather than firms' actions and performance indicators".…”
Section: Disclosure Theories Literature Review and Research Hypothesesmentioning
confidence: 99%
“…In selecting which specific types of communicative impression management tactics (i.e., corporate disclosures) to adopt, managers may give particular attention to the content, language and/or presentation of information, which can all be used with the objective of strategically manipulating the perceptions of stakeholders (Clatworthy and Jones, 2001;Yuthas et al, 2002;see Merkl-Davies and Brennan, 2007 for a complete review). Prior studies have documented the presence of certain language characteristics (Smith and Taffler, 2000;Sydserff and Weetman, 2002) or the effective use of verbal tone and language bias (Aerts, 1994;Cho et al, 2010; in corporate narratives.…”
Section: Tone and Language Of Corporate Disclosurementioning
confidence: 99%